Indian Agriculture Since Independence
Critically reviewing the performance of Indian agriculture since independence, the book examines the relative performance of Indian agriculture both during the plan period and post-reform period as well as the role of agriculture in the development of Indian economy. The book also underlines the main cause of deceleration of agriculture in the post-reform period and makes policy suggestions for regeneration of Indian agriculture.